2021
DOI: 10.1016/j.jmir.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspective on the online delivery of radiography & medical imaging program during COVID-19 pandemic

Abstract: Introduction : La pandémie de COVID-19 a entraîné d'importants changements dans la prestation des programmes universitaires dans le monde entier. Les cours magistraux en face à face (enseignement traditionnel) ont été remplacés par des sessions en ligne, enregistrées ou en direct; cependant, les systèmes en ligne ne constituent pas un substitut efficace aux cours cliniques ou de laboratoire. L'objectif de cette étude est d'évaluer le point de vue des étudiants en imagerie sur la sensibilisation à … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Ng 28 showed that despite these flexibilities, standards of radiography education were maintained as online open-book assessments presented no issues relating to academic integrity. However, other studies show that learning via the online delivery method increased students' stress levels and anxiety 26 , 29 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ng 28 showed that despite these flexibilities, standards of radiography education were maintained as online open-book assessments presented no issues relating to academic integrity. However, other studies show that learning via the online delivery method increased students' stress levels and anxiety 26 , 29 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 93%
“…In order to continue learning while movement was restricted, higher institutions transitioned from face-to-face delivery to an online delivery format. The benefits identified by students include flexibility and reduced cost of transportation and living, as some students could study from home while living with family rather than renting accommodation closer to university 26 , 27 . Ng 28 showed that despite these flexibilities, standards of radiography education were maintained as online open-book assessments presented no issues relating to academic integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid transition from classroom to online teaching and learning: According to the literature review, COVID-19 has an impact on medical imaging students' teaching and learning because of the quick switch to online instruction. Nine of the 14 studies [14][15][16][17][18][19][20][21][22] have covered this topic in their discussions. It was concluded by the participants in the study of Gumede and Badriparsad [14] that face-to-face instruction is superior to distance education.…”
Section: Emerged Themesmentioning
confidence: 99%
“…Traditional, face‐to‐face lectures were readily converted from in‐person to an online format, particularly at those institutions that had key electronic resources already blended into their curricula before the pandemic (Binks et al, 2021 ). However, online systems are not thought to be an effective substitute for an in‐person, hands‐on mode of instruction (Bowra et al, 2015 ; Alhasan & Al‐Horani, 2021 ; Zavitz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, online systems are not thought to be an effective substitute for an in-person, hands-on mode of instruction (Bowra et al, 2015;Alhasan & Al-Horani, 2021;Zavitz et al, 2021).…”
mentioning
confidence: 99%